115k views
1 vote
A)Solve the equation
2y^2-7y-4=0

b) Use your answer of part a to solve the equation
2(2^x)^2-7(2^x)-4=0

User Rmaxx
by
4.8k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

Given

2y² - 7y - 4 = 0 ← in standard form

(2y + 1)(y - 4) = 0 ← in factored form

Equate each factor to zero and solve for y

2y + 1 = 0 ⇒ 2y = - 1 ⇒ y = -
(1)/(2)

y - 4 = 0 ⇒ y = 4

(b)

Comparing this equation to the one given in (a) , then


2^(x) = y

Using the solutions from part (a)


2^(x) = -
(1)/(2) ( multiply both sides by - 1 )

-
2^(x) =
(1)/(2) [ note that
2^(-1) =
(1)/(2) ]

x = - 1


2^(x) = 4 [ note that 2² = 4 ]

x = 2

User Plindberg
by
5.2k points